Fifty-five per cent return to competitive sport following anterior cruciate ligament reconstruction surgery: an updated systematic review and meta-analysis including aspects of physical functioning and contextual factors. Issue 21 (25th August 2014) - Ardern, Clare L; Taylor, Nicholas F; Feller, Julian A; Webster, Kate E
Abstract : Background: The aim of this study was to update our original systematic review of return to sport rates following anterior cruciate ligament (ACL) reconstruction surgery. Method: Electronic databases were searched from April 2010 to November 2013 for articles reporting the number of patients returning to sport following ACL reconstruction surgery. Return to sport rates, physical functioning and contextual data were extracted and combined using random-effects meta-analyses. Data from the original review (articles published up to April 2010) were combined with data from the updated search. Results: Sixty-nine articles, reporting on 7556 participants, were reviewed. On average, 81% of people returned to any sport, 65% returned to their preinjury level of sport and 55% returned to competitive level sport after surgery. Symmetrical hopping performance (d=0.3) and the contextual factors of younger age (d=−0.3), male gender (OR=1.4), playing elite sport (OR=2.5) and having a positive psychological response (d=0.3) favoured returning to the preinjury level sport. Receiving a hamstring tendon autograft favoured returning to competitive level sport (OR=2.4), whereas receiving a patellar tendon autograft favoured returning to the preinjury level sport (OR=1.2). Conclusions: Returning to sport varied according to different physical functioning and contextual factors, which could warrant additional emphasis in postoperative rehabilitation programmes to maximise participation.